Tindakan Cyberbullying Di Media Sosial Hukum Dan Masyarakat - Majiyatun Nisa; Taun Taun (Hakim, 2024)
The rapid development of science and technology (IPTEK) in people's lives can lead to the emergence of new ideas for committing crimes. Criminals utilize technological advances, especially in communication tools that contain various kinds of social media. The presence of social media provides a large enough gap in shaping the behavior of a society, especially in adolescents. Habits and social environment have an influence in using social media because they are supported by tools such as cellphones to access cyberspace. A crime that has often occurred is cyberbullying, which is an act of online bullying because the perpetrator carries out the bullying through social media. Cyberbullying has a psychological impact on its victims. In this research, the author uses data collection methods from research journals, e-books and legal articles. This research aims to analyze the influence of social media in people's lives, especially for teenagers and the appropriate punishment for cyberbullying perpetrators.